The Effects of Land Use Change upon Hydrological Balance Components in Kordan Basin Using HEC- HMS Model - Mojtaba Yamani; Akbar Mehrjonezhad (جغرافیا و پایداری محیط)
Changes in the land use adversely affect the Hydrological processes in a catchment and disrupts the natural water balance. In this study, changes in the hydrological components of Kordan watershed due to the land use change have been studied in the years 1987 and 2000 and 2011. According to the research method used, at first the land use layers for the three mentioned years were obtained from the Landsat Thematic Mapper (TM) using the supervised classification method. The rainfall, Flow and daily temperature data, along with the monthly evaporation of Najmabad station was used to simulate the rainfall-runoff with HEC-HMS model. In the basin model component, the SCS Curve Number and SCS Unit Hydrograph were used respectively for the loss and transform methods; the Specified Hyetograph was used in the meteorological model too. Simulation results showed that the runoff coefficient has been increased from 71.38 percentage in 1987 to 73.71 percentage in 2000 and 77.89 percentage 2009.